(untitled) (The Journal of Medicine, Humanity and Media, 2025)
This study evaluates the Omnimedia matrix rumor refutation model’s effectiveness during public health emergencies, particularly COVID-19. The model integrates mainstream, platform, and self-media to counter misinformation comprehensively. Key findings emphasize mainstream media’s role in verifying and debunking rumors, with support from platform and self-media for rapid information dissemination. Vertical coordination involves central and local media, while horizontal collaboration ensures optimized content across platforms. This model offers a structured approach to rumor refutation, enhancing information reliability and public trust, providing a valuable framework for managing misinformation in future crises​​.